The effects of CSR report mandatory policy on analyst forecasts: Evidence from Taiwan - Tzu-Yun Tseng; Niensu Shih (Journal of Risk and Financial Management, 2022)
The Taiwanese government altered its corporate social responsibility (CSR) report management policy from voluntary disclosure and assurance of CSR reports to partial mandatory disclosure and partial mandatory assurance. This paper examines this policy's effects on analyst forecast. The empirical results showed that the mandatory disclosure policy on CSR reports significantly increased analyst forecast accuracy and reduced analyst forecast dispersion. Furthermore, the study found that analyst forecast accuracy was further increased when CSR reports were forced to undergo accountant assurance than those without mandatory accountant assurance which means that the mandatory assurance policy on CSR reports significantly further increased analyst forecast accuracy.
Keywords: 650; analyst forecast accuracy; analyst forecast dispersion; corporate social responsibility reports; mandatory assurance; mandatory disclosure